Development of a physiotherapy-led balance clinic: the Aintree model. Issue 11 (November 2014) - Kasbekar, A V; Mullin, N; Morrow, C; Youssef, A M; Kay, T; Lesser, T H
Abstract Objective: To create a 'one-stop' clinic in which assessment, diagnosis, treatment and therapies for most patients presenting with balance and dizziness disorders are delivered simultaneously. Methods: Patients triaged via referral letters were selected to attend the balance clinic, which is led by specialist balance physiotherapists. Patients were seen by an audiologist, and a 'balance' ENT consultant was available for joint consultations when required. Further details of the clinic set up are discussed. Results: Over an 18-month period, 200 new 'dizzy' patients attended the clinic. Benign paroxysmal positional vertigo and labyrinthitis were the commonest diagnoses. Fifty per cent of all patients were discharged after a single clinic visit. Questionnaires showed that patient satisfaction was high. Conclusion: The physiotherapy-led balance clinic has reduced patient waiting times to be seen, has a high level of patient satisfaction and is economically beneficial.